Detection of basement membrane components and basal cell keratin 14 in noninvasive and invasive carcinomas of the breast. - Wetzels, R. H. (1989)
Using immunohistochemistry, the distribution patterns of basement membrane components type VII collagen (monoclonal antibody LH7.2), type IV collagen, and laminin were investigated in normal and malignant human breast tissue and compared with that of keratin 14 (monoclonal antibody LL002), which is expressed only by the basal (myoepithelial) cells in the secretory epithelia of the mammary gland. In normal breast tissue as well as in intraductal carcinomas, a more or less continuous basement membrane was observed at the epithelial stromal interface. Unlike laminin and type IV collagen, type VII collagen was not detected in the basement membrane of blood vessels. The keratin 14 antibody stained the basal cell layer of normal ducts and ducts with in situ cancer. In 85% of the invasive carcinomas no basement membrane or basal cells were detected. In 13 cases, however, laminin, type IV collagen, and/or type VII collagen were detected around tumor nests and individual tumor cells. Five of these tumors also showed a positive reaction with the keratin 14 antibody. In five cases keratin 14 expression was found without detectable basement membrane components. It is concluded that 18 of 103 invasive ductal breast carcinomas examined in this study exhibit a basal cell phenotype as determined from the expression of keratin and the deposition of basement membrane components.